Does state aid for broadband deployment in rural areas close the digital and economic divide? - Wolfgang Briglauer; Niklas S. Dürr; Oliver Falck; Kai Hüschelrath (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
We evaluate the impact of a major European state aid program for broadband deployment applied to rural areas in the German State of Bavaria in the years 2010 and 2011. Using difference-in-differences estimation strategies, we find that aided municipalities have - depending on broadband quality - a between 16.8 and 23.2 percent higher broadband coverage than non-aided municipalities. This increase in broadband coverage - closing the digital divide - results in an increase of on average seven employed individuals living in the respective aid-receiving municipalities while leaving the number of employed or selfemployed individuals or wages unaffected. We therefore conclude that an increase in broadband coverage through state aid prevents rural areas from depopulation, but does not contribute to a further closing of the economic divide in the form of creating new jobs.
urn:nbn:de:bsz:180-madoc-414942
Keywords: D62; D73; G38; H23; J23; K23; L52; L96; L98; R23; 330; government policy; state aid; ex-post evaluation; broadband; employment; rural areas; European Union; Germany; Bavaria